Seasonal variation in arterial blood pressure. - Brennan, P J (1982)
Blood pressure measurements recorded during the medical Research Council's treatment trial for mild hypertension have been analysed according to the calendar month in which the readings were made. For each age, sex, and treatment group systolic and diastolic pressures were higher in winter than in summer. The seasonal variation in blood pressure was greater in older than in younger subjects and was highly significantly related to maximum and minimum daily air temperature measurements but not to rainfall.